Development of Achalasia in a Patient With Chronic Intestinal Pseudo-Obstruction. Issue 6 (3rd June 2022) - Kwon, Joshua; Koop, Andree; Francis, Dawn
ABSTRACT: Development of concurrent achalasia and chronic intestinal pseudo-obstruction (CIPO) is rare, although esophageal dysmotility is common in patients with CIPO and may suggest worse clinical outcomes. We present a case of a 63-year-old man with a 15-year history of CIPO who developed postprandial regurgitation, vomiting, and dysphagia and was diagnosed with achalasia through radiographic and endoscopic findings. This is only the third case in the reported literature that involves both conditions. Rather than representing 2 separate disorders, CIPO and achalasia may instead represent neurogenic variants of 1 underlying condition affecting the myenteric plexus.